Genome-wide identification of candidate chemosensory receptors in the bean bug Riptortus pedestris (Hemiptera: Alydidae) and the functional verification of its odorant receptor co-receptor (Orco) in recognizing aggregation pheromone - Liu, Panjing; Guo, Jianglong; Wei, Hongyi; Feng, Likai; Gao, Zhanlin; Zhang, Tao (Frontiers in Physiology, 2023)
A sophisticated and sensitive olfactory system plays a vital role in the survival and reproduction of insects. Chemosensory receptors are indispensable for the molecular recognition and discrimination of semiochemicals. Riptortus pedestris is a notorious pest of legume plants, resulting in yield losses and quality decreases in soybeans. It is well accepted that R. pedestris highly relies on its olfactory system in detecting aggregation pheromones, host volatiles, and pesticides; however, little research focused on its chemosensory receptors. In the present study, we identified 237 odorant receptors (ORs), 42 gustatory receptors (GRs), and 31 ionotropic receptors (IRs) from the reported genome of R. pedestris, and analyzed their phylogenetic relationship with other hemipteran species. Through the results of RNA-seq and real-time quantitative PCR (qRT-PCR), we found that RpedORs displayed different expression levels in the antennae of R. pedestris at different development stages. To further verify the function of odorant receptor co-receptor (Orco), an obligate and unique insect OR, we silenced2 RpedOrco by RNA interference (RNAi) method. The results showed that silencing RpedOrco could significantly impair the response to aggregation pheromone in R. pedestris, indicating that RpedOrco plays an essential role in odorant detection. Our results can provide the theoretical foundations for revealing the olfactory recognition mechanism of R. pedestris and help explore and develop novel olfactory-based agents against this pest.